Unveiling the practices and challenges of professional learning community in a Malaysian Chinese Secondary School - Wei, Chuan Chua; Lei, Mee Thien; Shun, Yi Lim; Chee, Seng Tan; Teik, Ee Guan (SAGE Publications, 2020)
Professional learning community (PLC) studies in the Asian Chinese nations remain scarce despite the emerging interest in the practice of PLC beyond the Western context. This study attempts to provide an understanding of the practices of PLC and challenges in implementing PLC in a Malaysian Chinese culture–dominated secondary school. This qualitative study used a phenomenological constructivist approach as a strategy of inquiry. Semi-structured interview data were collected from six middle leaders and ordinary teachers in a national-type Chinese secondary school in the northern region. Findings informed three existing PLC practices at the school level, namely, (a) peer coaching, (b) sharing of personal practices, and (c) professional development courses. However, the practice of PLC encounters various challenges, including excessive workload, teachers’ passive attitudes, unsupportive conditions in the school, poor execution of PLC by the school community, and a vague understanding of PLC. Interestingly, this study identified two uncovered challenges hindering the development of PLC: misconception about PLC and lack of supervision from the authority. Implications and future studies are presented.